Analisis Dampak Sertifikasi Guru terhadap Kualitas Pembelajaran PAI di MAN Sidoarjo - Cinta Aprilia Putri; Eki Purwo Maharani; Fathur Rohman (MAN 4 Kota Pekanbaru, 2026)
Teacher certification is a government initiative aimed at improving professionalism and the quality of education; however, its impact in educational practice still requires continuous evaluation. This study aims to analyze the impact of teacher certification on the quality of Islamic Religious Education (IRE) learning at MAN Sidoarjo, particularly in terms of instructional method innovation and the use of learning media. The research employed a descriptive qualitative method with data collected through participatory observation, documentation, and in-depth interviews involving IRE teachers, students, and school administrators. The findings reveal that teachers who obtained certification in 2025 experienced significant transformation in the learning process, marked by a shift from lecture-based methods to project-based and inquiry-based learning approaches. In addition, there was strong integration of digital technology through the use of AI-based media, microsites, and Quizizz to enhance classroom interaction. Nevertheless, learning effectiveness still faced several challenges, including the heterogeneity of students’ educational backgrounds and limited instructional time during afternoon classes. The study concludes that teacher certification has proven effective in improving the pedagogical competence and digital literacy of PAI teachers, which directly contributes to students’ understanding and learning enthusiasm at MAN Sidoarjo.